Using “Insider Econometrics” to Study Productivity - Bartel, Ann; Ichniowski, Casey; Shaw, Kathryn (American Economic Review, 2004)
Griliches’ 1994 presidential address considers the limited success economists had in trying to account for the productivity slowdown of the 1970’s and 1980’s, and “urges us toward the task of observation and measurement.” In the 1990’s, the high rates of productivity growth emphasized the need for new models of productivity, this time turning to estimating organization-level determinants of productivity focusing on businesses’ use of new computerbased information technologies (IT), and new methods of work organization (Timothy Bresnahan et al., 2002). In this paper, we take up the charge to develop new data and new methods for modeling the productivity of organizations. We summarize three methods for assembling data for an “insider econometrics” study of the productivity of organizations, and we illustrate one method that we refer to as “informed survey analysis.”